Analisis Penerapan Standar Akuntansi Pemerintah Berdasarkan PP No. 71 Tahun 2010 Pada Dinas Pekerjaan Umum Bina Marga dan Tata Ruang Provinsi Sumatera Selatan - Sri Hartati; Edduar Hendri; Emma Lilianti (Jurnal Media Akuntansi (Mediasi), 2020)
ABSTRACT The purpose of this study is to analyze the application of government accounting standards based on PP. 71 of 2010 At the Public Works Office of Bina Marga and Spatial Planning of South Sumatra Province which is analyzed through Financial Statements, Information Systems / Devices used and Organizational Commitment Performance time is to determine the obstacles in the Application of PP No.71 of 2010 concerning Accrual-Based Government Accounting Standards just implemented in 2018. This type of research is qualitative descriptive research. This research was conducted by taking an object at the Public Works Office of Bina Marga and Spatial Planning of South Sumatra Province, which is located at Jalan Ade Irma Nasution No. 10 Palembang. The types of data used in this study are primary data and secondary data. Methods of data analysis using descriptive analysis. Based on data analysis, the implementation of SAP Public Works Office of Highways and Spatial Planning of South Sumatra Province which is indicated by Commitment, Information Systems / Devices used is concluded that seen from the preparation of financial statements not based on PP. 71 Year 2010, the Information System / Tool used is SIMDA Version 2.7.7 which has been accrual based but still needs socialization in its application as well as Organizational Commitment that supports the accrual-based government regulation. Keywords: Accrual Based SAP, Implementation of PP No. 71 of 2010 ABSTRAK Tujuan penelitian ini adalah untuk menganalisis Penerapan Standar Akuntansi Pemerintah Berdasarkan PP No. 71 Tahun 2010 Pada Dinas PU Bina Marga dan Tata Ruang Provinsi Sumatera Selatan yang dianalisis melalui Laporan Keuangan, Sistem Informasi/Perangkat yang digunakan dan Komitmen Organisasi.Time kinerja untuk mengetahui kendala dalam Penerapan PP No.71 Tahun 2010 tentang Standar Akuntansi Pemerintah Berbasis Akrual yang baru diterapkan pada tahun 2018. Jenis penelitian adalah penelitian deskriptif kualitatif. Penelitian ini dilakukan dengan mengambil objek pada Dinas PU Bina Marga dan Tata Ruang Provinsi Sumatera Selatan yang beralamat di Jalan Ade Irma Nasution No. 10 Palembang. Jenis data yang digunakan dalam penelitian ini adalah data primer dan data sekunder. Metode Analisis data menggunakan analisis deskriptif. Berdasarkan analisis data maka Penerapan SAP Dinas PU Bina Marga dan Tata Ruang Provinsi Sumatera Selatan yang diindikasikan dengan Komitmen, Sistem Informasi/Perangkat yang digunakan disimpulkan bahwa dilihat dari penyusunan laporan keuangan belum berdasarkan PP No. 71 Tahun 2010, Sistem Informasi/Perangkat yang digunakan adalah SIMDA Versi 2.7.7 yang telah berbasis akrual tetapi masih perlu untuk diadakan sosialisasi dalam penerapannya serta Komitmen Organisasi yang mendukung dengan adanya peraturan pemerintah berbasis akrual tersebut. Kata Kunci :  SAP Berbasis Akrual , Penerapan PP No. 71 Tahun 2010